Oil Price Changes and U.S. Real GDP Growth: Is this Time Different? - Lanouar Charfeddine; Tony Klein; Thomas Walther (Queen's University Belfast, Queen's Management School, 2018)
This paper contributes to the large debate regarding the impact of oil price changes on U.S. GDP growth. Firstly, it replicates empirical findings of prominent studies and finds that the proposed oil price measures have a dissipating effect with recent data up to 2016Q4. Secondly, it re-examines the issue and provides evidence that oil price decreases affect the GDP growth, when taking into consideration mixed data sampling technique. Finally, it puts particular focus on nonlinearity and a possible instability and shows that combining Markov switching and mixed data sampling models allows to identify different regimes permanently changing with the Great Moderation.
Keywords: C24; E32; F43; Q43; 330; Oil prices; GDP growth; Asymmetry; Nonlinearity; Markov switching models; Mixed Data Sampling